2011
DOI: 10.1128/aem.01467-10
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Penalties Associated with Inducible Tolerance in Helicoverpa armigera to Insecticidal Toxins from Bacillus thuringiensis

Abstract: Exposure of insect larvae to sublethal concentrations of crystal toxins from the soil bacterium Bacillus thuringiensis (Bt toxins) causes the induction of immune and metabolic responses that can be transmitted to offspring by epigenetic inheritance mechanisms. Given that the elevated immune status carries significant developmental penalties, we wanted to establish the relationships between immune induction, tolerance to the toxin and developmental penalties. A laboratory culture of Helicoverpa armigera was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
6
0
2
Order By: Relevance
“…Oral Btt infection did not decrease survival in our study but was associated with slower development in T. castaneum larvae, indicating a direct cost of infection or an indirect cost from mounting an immune response, as previously observed in the same system (Tate & Graham, 2015) and in other insects challenged with Bt toxins (HernĂĄndez-MartĂ­nez et al, 2017; Rahman et al, 2011). Previously documented variation in resistance in T. castaneum against Cry3 proteins effective against other Tenebrionid beetles may explain why Btt had negative effects on development but did not instigate high mortality (Milutinović et al, 2013; Oppert et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Oral Btt infection did not decrease survival in our study but was associated with slower development in T. castaneum larvae, indicating a direct cost of infection or an indirect cost from mounting an immune response, as previously observed in the same system (Tate & Graham, 2015) and in other insects challenged with Bt toxins (HernĂĄndez-MartĂ­nez et al, 2017; Rahman et al, 2011). Previously documented variation in resistance in T. castaneum against Cry3 proteins effective against other Tenebrionid beetles may explain why Btt had negative effects on development but did not instigate high mortality (Milutinović et al, 2013; Oppert et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…A Cry1Ac tolerant strain of H. armigera was produced in 2009 (Rahman et al ., ) by culturing the larval stages of susceptible insects on the artificial diet with the surface coated (using a pipette) with 0.1 mg mL −1 HD73 bacterial lysate (see above) to provide exposure to a sub‐lethal dose of Cry1Ac toxin. During establishment of the tolerant population, bioassays were performed every five generations to confirm and measure the level of tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…A bacterial lysate containing Cry1Ac toxin produced from B. thuringiensis strain kurstaki HD73 was supplied by John L. Reichelt (Bacterial Fermentation Pty Ltd, Australia) and was prepared and assessed as described by Rahman et al (2011). The suspension was stored at −20 ∘ C and was thawed before dilution with sterile ultrapure water (Milli-Q; Merk Millipore, Germany) to produce a 20 mg mL −1 protein suspension, which was stored for short periods at 4 ∘ C prior to use.…”
Section: Cry1ac Toxin Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the levels of DNA methylation and histone acetylation of this resistant strain are increased, with the expression levels of some conserved miRNAs and their target mRNAs significantly changed, indicating that epigenetic mechanisms mediate the evolution of G. mellonella resistance to Bt at pre-transcriptional and posttranscriptional levels ( Mukherjee et al, 2017 ). Another evidence comes from the cotton bollworm ( Helicoverpa armigera ), which, when continuously exposed to Cry1Ac toxin for 12 generations, reveals tolerance to Cry1Ac with enhanced immune status through an epigenetic mechanism from a strong maternal effect, which can be passed to its offspring ( Rahman et al, 2011 ). Besides, the red flour beetle ( Tribolium castaneum ) exhibits an increased survival rate after exposure to Bt in a short time that can be directly transmitted to the first (F1) and second filial (F2) generations, called paternal trans-generational immune priming, which may be regulated by epigenetic mechanisms too ( Eggert et al, 2014 ; Schulz et al, 2019 ).…”
Section: The Resistance Mechanisms Of Insects Against Cry Toxinsmentioning
confidence: 99%